Agriculture the food we grow and animals we raise - Casper, Julie Kerr (Natural resources, 2007)
A comprehensive introduction to U.S. agricultural practices. The chapters cover the history of American farming to sustainable practices for the future. Includes tables, diagrams, a glossary and chronology.